PEMBUATAN APLIKASI SALES FORCE AUTOMATION (SFA) BERBASIS MOBILE PADA PT NOVA TEKNOLOGI AWANI - Ricky Soeputra; Zyad Rusdi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
PT. Nova Technology is a company engaged in technology in several sections, such as Food and Beverage, Retail, and several others. So companies need an application that helps manage sales schedules. Therefore the purpose of making this application is to make it easier for the head of sales to arrange a schedule. And a feature to approve a quotation until there is a feature for tracking sales via GPS. In addition, there are several other supporting features, namely for registering brands and branches, viewing brand and branch data, making edits to brands and branches, and a feature to view a list of data lists owned by PT. Nova Technology Awani.